Exploring Destination Branding: Tourist Interests in Cibaduyut’s Creative Urban Village - Tonda, Yoseph Maxidiaz Corala; Rangga, Paulus Pradipta; Florentyna, Dyta Nadya; Darmanto, Rayner Evan; Hermawan, Daniel (BIMA Journal (Business, Management, & Accounting Journal), 2024)
Purpose: As a creative city, Bandung has several creative tourism urban villages. One of them, Cibaduyut Creative Tourism Urban Village has its destination brand as trademark, especially Shoe Monument (Tugu Sepatu). The disappearance of Shoe Monument became the central phenomenon studied tourist interest to visit Cibaduyut Creative Tourism Urban Village. Methodology: This research uses a quantitative descriptive approach using Statistical Product and Service Solutions (SPSS) tools with 107 respondents. Influence of the dimensions of destination brand on tourist interest studied here. Results and Findings: Brand identity, brand essence, brand character, brand personality, brand culture, and brand image have a strong significance in tourist interest. Findings: Destination brands have a role to support the tourist interest in tourism destinations. Brand essence dimension have the biggest contribution in tourist interest. Novelty and Originality: The importance of Shoe Monument, also destination branding evolution to address tourist interest. Originality:  Emphasized destination brand should be viewed as a symbol or process that is always evolving. Conclusion: Brand identity, brand essence, brand character, brand personality, brand culture, and brand image have a strong significance on tourist interest. Local authorities in Cibaduyut cooperation with Bandung’s city government should enhance destination brand aspect to attract tourist interest. Type of Paper: Empirical Research Paper.